Simulação numérica de laminação da liga para implantes cirúrgicos ASTM F138 - Magro, Douglas Strini (2010)
The hot rolling process is a kind of industrial method used in raw material manufacturing for surgical implant pieces. The hot rolling processing has been the subject of many studies and the knowledge of this process is very well established. However, this process requires the control of several parameters such as the geometry of billets and rolling rolls, the initial and finishing deformation temperatures and strain rates, pass schedule, total reduction of rolling process and the capacity of the equipment. The most important feature of the metallurgical processing is the final quality of the produced material, since all parameters described above act upon processing and they can change the material behavior. Therefore, the best would be that all the process parameters were well known and controlled. The aim of this work was to analyze how the rolling processing parameters like temperature, deformation, strain rate and stress level vary during hot rolling of an ASTM F138 alloy billets. This analysis was conducted using a commercial software based on finite elements methods developed for hot work processing simulation. The processing data were attained from an industrial plant and two similar passes of a hot rolling schedule were simulated. The first pass promoted the change of a billet from a square geometry to an oval shape and the second from oval to round shape. The evolution and distribution of strain, strain rate, temperature and stress throughout the billets during hot rolling were determined and analyzed. The results showed that the numerical simulation was efficient to describe parameter evaluations, since the results are similar to those observed in a real rolling processing. The achieved results can be used as a data base for analysis of defects and failures upon processing and also to progressive improvement of the industrial processing.